A novel approach based on solvent displacement crystallisation for iron removal and copper recovery from solutions of semi-pilot scale bioleaching of WPCBs. (20th April 2021) - Erust, Ceren; Akcil, Ata; Tuncuk, Aysenur; Deveci, Haci; Yazici, Ersin Yener; Panda, Sandeep
Abstract: Bioleaching of copper from electronic waste (e-waste) in the form of high grade waste printed circuit boards (WPCBs) collected from obsoletemobile phones is assessed using a consortium of iron (Fe 2+ ) & sulfur (S°) oxidizing bacteria in a semi-pilot reactor system. Results from the study indicated that the microorganisms were able to grow in the presence of WPCB and efficiently solubilize Cu from it. At a solid/liquid ratio of 10% (w/v)with a particle size of <250 μm, maximum bioleaching efficiency of around 95% Cu was observed in 8 days of leaching under oxidation-reduction potentials (ORP) of >600 mV and pH 1.8. In order to recover the metallic values, electrowinning (EW) of copper from the bioleach solutions was investigated in detail. Direct EW of the bioleach solution yielded low current efficiencies (66.1% over 4 h.), ascribed due to the high concentrations of iron (i.e., 9.1 g/L). As a novel approach, a downstream purification and concentration process was further tested, that involved ferric hydroxide (Fe(OH)3 ) precipitation and solvent displacement crystallisation (SDC) to eliminate iron and increase the concentration of copper in solution prior to its application for EW. This significantly improved the current efficiency (by ∼22%) during the EW of copper. A process flow-sheet for Cu recovery from WPCBs was developed and the downstream process was found to be profitable even though its margin was small with techno-economic analysis. It is believed that the two-step hybrid process i.e. bioleaching technique followed by the novel approach proposed (i.e., iron precipitation + SDC) can be suitably employed for the extraction of copper from WPCBs. Graphical abstract: Schematic representation of the different methods tested for EW operation – Development of a novel Bio-Hydrometallurgical processes. Image 1 Highlights: 95% Cu was bioleached from WPCB using a consortium of iron & sulfur oxidizing bacteria in a semi-pilot reactor system. Combinations of bio/hydro/electro-metallurgy were tested for Cu extraction from WPCB. Different electrowinning routes were proposed for bioleaching solution in Cu extraction. A novel downstream process for Cu recovery was established in the study. The techno-economic feasibility studies showed that the recycling of WPCBs is a feasible process.